Sistem Informasi Pelayanan Jemaat Gereja Berbasis Website Menggunakan Analisis PIECES - Yuni Retno Asih; Adhi Priyanto; Daniel Alfa Puryono (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
The church is a spiritual institution for Christians. In the church there are various kinds of service activities, such as catechism services, baptism services, wedding blessing services, and social service services. In general, the Church in processing congregational service data, catechism data, baptismal data, marriage data is still recorded in the books, so that data can be lost or damaged, and it is less effective in searching data, because it takes a long time. In providing information such as worship agendas, church activities, and other routine church activities, it is still manual, namely through congregation bulletins. The purpose of this research is to build a website-based church service system model to support the implementation of various church services more effectively and efficiently. This study uses the PIECES analysis method to check and analyze the advantages and disadvantages that exist in the system. This system is designed using UML, to make it easier to design a website-based system. This church service information system provides features of church service activities and more complete information about the church that can be accessed more practically anytime and anywhere.